Data Access Control and Secured Data Sharing Approach for Health Care Data in Cloud Environment. - Pugazhenthi, A.; Chitra, D. (Journal of Medical Systems, 2019)
One of the vital hitches in today's world of research is ensuring the security of the Cloud. This security can be ensured by inventing new techniques that may possibly help in safeguarding and assuring the optimal status of information in the cloud. Contents that are stored in the Cloud are majorly affected by the attempts made by illegitimate sources that are trying to access it. The security level of the contents that are stored in the cloud can be guaranteed by focusing on a task that helps in both securing and verifying the data. In order to manage the security level, (SE-KAC) which is also known as Scalable and Enhanced Key-Aggregate Cryptosystem was initiated in current research method. But this method of securing and sharing secret keys cannot be used in the stage of decryption. However this problem can be resolved in proposed method since it introduces sharing of the data securely using a method called Improved Diffie Hellman Key Exchange Algorithm (IDHKE). By introducing the Improved Diffie Hellman Key Exchange Algorithm, securely sharing the secret keys to the receivers of the data has been achieved. The secret key details can be exchanged securely using this method. By this means it makes sure its affirmations. Here the key is safely generated using one random prime number, a master secret key and parameter value. Intended for the secured and consistent access control limitation, an encryption which is attribute-based is used. The proposed method thus ensures the protected data transmission with exact and trustworthy validation.